2023
DOI: 10.1530/ec-23-0024
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, mortality, and socioeconomics in Klinefelter syndrome and 47,XYY syndrome: a comparative review

Abstract: Context Klinefelter syndrome (KS, 47,XXY) and 47,XYY syndrome are genetic conditions characterized by a supernumerary sex chromosome. The conditions share many traits, but considerable phenotypic differences are seen between the two. Focusing on morbidity, mortality, and socioeconomics, this review highlights similarities and differences. Methods Relevant literature was identified through PubMed with the following search terms; 'Klinefelter', '47,XXY', '47,XYY', and 'Jacobs syndrome'. Included journal articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 91 publications
3
9
0
Order By: Relevance
“…Our results corroborate findings from multiple other studies that associate SCAs with excess morbidity and higher health care utilization . Men with 47,XXY, independent of a known clinical diagnosis, were more likely than controls to endorse a history of numerous medical and psychological conditions, most of which have been previously reported and serve as external validation of our results .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results corroborate findings from multiple other studies that associate SCAs with excess morbidity and higher health care utilization . Men with 47,XXY, independent of a known clinical diagnosis, were more likely than controls to endorse a history of numerous medical and psychological conditions, most of which have been previously reported and serve as external validation of our results .…”
Section: Discussionsupporting
confidence: 92%
“…Our results corroborate findings from multiple other studies that associate SCAs with excess morbidity and higher health care utilization . Men with 47,XXY, independent of a known clinical diagnosis, were more likely than controls to endorse a history of numerous medical and psychological conditions, most of which have been previously reported and serve as external validation of our results . We also observed worse self-reported health and well-being metrics among men with SCA, which is congruent with current research, in which lower QOL outcomes are widely reported in individuals with SCAs .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations